2022
DOI: 10.1096/fj.202100186rr
|View full text |Cite
|
Sign up to set email alerts
|

SMPDL3b modulates radiation‐induced DNA damage response in renal podocytes

Abstract: The kidneys are radiosensitive and dose-limiting organs for radiotherapy (RT) targeting abdominal and paraspinal tumors. Excessive radiation doses to the kidneys ultimately lead to radiation nephropathy. Our prior work unmasked a novel role for the lipid-modifying enzyme, sphingomyelin phosphodiesterase acid-like 3b (SMPDL3b), in regulating the response of renal podocytes to radiation injury.In this study, we investigated the role of SMPDL3b in DNA double-strand breaks (DSBs) repair in vitro and in vivo. We as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…All the above proteins were validated, and results indicated that PADI4, IGF2, SMPDL3B, UHRF1, ANXA8, MK167, SLC39A4, LIMD1 and GJA1 were signi cantly upregulated in experimental group compared to the control group. SMPDL3B, ANXA8, MK167, SLC39A4, LIMD1 are mainly related to the occurrence, development and treatment of renal podocyte injury, lung cancer, melanoma, gallbladder cancer, etc [13][14][15][16][17] . However, the function of the PADI4, IGF2, UHRF1, DEFB4 and GJA1 in AELP is unknown and further investigation is needed.…”
Section: Discussionmentioning
confidence: 99%
“…All the above proteins were validated, and results indicated that PADI4, IGF2, SMPDL3B, UHRF1, ANXA8, MK167, SLC39A4, LIMD1 and GJA1 were signi cantly upregulated in experimental group compared to the control group. SMPDL3B, ANXA8, MK167, SLC39A4, LIMD1 are mainly related to the occurrence, development and treatment of renal podocyte injury, lung cancer, melanoma, gallbladder cancer, etc [13][14][15][16][17] . However, the function of the PADI4, IGF2, UHRF1, DEFB4 and GJA1 in AELP is unknown and further investigation is needed.…”
Section: Discussionmentioning
confidence: 99%
“…A single dose of radiation increases a variety of ceramide species, decreasing SMPDL3b expression, and decreasing S1P levels in podocytes. The overexpression of SMPDL3b in podocytes prevents these alterations and prevents cytoskeletal rearrangements, reduces reactive oxygen species generation, and improves double-strand break repair associated with radiation treatment, suggesting a protective effect [ 123 , 124 , 125 ].…”
Section: Sphingolipids In Podocytesmentioning
confidence: 99%
“…One of the most extensively researched elements of this molecule is its crucial function in the kidney. The overexpression of SMPDL3B protects versus radiation-induced changes in nuclear ceramide-1-phosphate (C1P) and ceramide levels, which has been linked to a unique role for the protein in DNA damage responses [ 12 ]. SMPDL3B has been shown to be a viable therapeutic target for various disorders and plays a significant role in the onset and progression of a number of diseases.…”
Section: Introductionmentioning
confidence: 99%